1986
DOI: 10.2754/avb198655010023
|View full text |Cite
|
Sign up to set email alerts
|

Basic Qualitative Parameters of Cow Colostrum and Their Dependence on Season and Post Partum Time

Abstract: Klimes J., P. Jagos, J. Bouda, S. Gajdusek: Basic Qualitative Parameters of Cow Colostrum and their Dependence on Season and Post ParIum Time. Acta vet. Hrno, 55,1986: 23-39.Under conditions of large scale' dairy unit for 2144 cows 19 physicochemical and biochemical parameters of cow colostrum and the influence of season and time after parturition on these parameters have been studied. Average samples of colostrum from the first milking, on the 3rd and 5th day post parturition were collected from cows -cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
20
8
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 18 publications
10
20
8
1
Order By: Relevance
“…Several authors have reported similar trends, i.e. that the pH of colostrum is low initially and increases with time post-partum (Klimes et al 1986;Madsen et al 2004;Tsioulpas et al 2007;Jeong et al 2009). The precise reason for the low pH of colostrum is unknown.…”
Section: Ph and Buffering Capacitymentioning
confidence: 53%
See 2 more Smart Citations
“…Several authors have reported similar trends, i.e. that the pH of colostrum is low initially and increases with time post-partum (Klimes et al 1986;Madsen et al 2004;Tsioulpas et al 2007;Jeong et al 2009). The precise reason for the low pH of colostrum is unknown.…”
Section: Ph and Buffering Capacitymentioning
confidence: 53%
“…A low level of lactose in early post-partum milkings, followed by a steady increase thereafter, until a normal level is reached, has been reported by several authors (Parrish et al 1948(Parrish et al , 1950Klimes et al 1986;Madsen et al 2004;Kehoe et al 2007;Tsioulpas et al 2007;Georgiev 2008;El-Fatah et al 2012;Morrill et al 2012). Lactose concentrations as low as 1.2% have been reported in colostrum (Kehoe et al 2007;Morrill et al 2012).…”
Section: Lactosementioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Klimes et al (1986) failed to find a correlation between calcium and phosphorus content and protein concentration in bovine colostrum whey; this is in contrast with the results reported by Gaucheron (2005), who found a significant positive correlation between these parameters in whole milk. These findings lead to the conclusion that the correlation between calcium and inorganic phosphorus and protein fraction of colostrum and milk is due to the interactions between these minerals and casein.…”
contrasting
confidence: 56%
“…As in the study of Klimes et al (1986), the levels of constituents such as calcium, magnesium, and inorganic phosphorus were much higher at the first milking postpartum. Kume and Tanabe (1993) reported that the colostrum concentrations of calcium, phosphorus, and magnesium were higher immediately after calving and decreased rapidly in the subsequent 24h, which is in contrast with the findings of the present study in which the concentration of these elements also decreased, but in a much slower fashion.…”
mentioning
confidence: 71%